Adaptation of the Five-by-Five Resilience Scale in Indonesian - Syafira Ainnur Rahmah; Adinda Tasya Kamila; Faikh Kheni Angraeni; Fikriyanti Elfrianita Firmani; Jihan Salsabila Ramadhayanti; Dian Sari Utami (Publikasi Indonesia, 2024)
Resilience is the ability of individuals to be able to adapt and rise from difficult conditions or situations. The Five-by-Five Resilience Scale is a measurement tool developed by DeSimone et al (2016) to measure individual resilience. There are five protective factors of resilience, namely adaptation, emotional regulation, optimism, self-efficacy and social support. This research aims to adapt the Five-by-Five Resilience Scale into Indonesian. This research was conducted because there has been no testing of the Indonesian version of the Five-by-Five Resilience Scale. The subjects involved in the study were 267 subjects with an age range of 18 - 25 years who were domiciled in Indonesia. Based on the results of psychometric testing through Exploratory Factor Analysis (EFA), 4 factors were obtained that build the Five-by-Five Resilience Scale. The results also show that the Five-by-Five Resilience Scale has a correlation with other measuring tools in convergence validity testing. The reliability test results show that the dimensions on the Five-by-Five Resilience Scale as a whole have a reliability > 0.7.